Condensation in the readings of poems seasoned poets ( An analytical study ) (Journal of the College of Basic Education, 2022)
Poetry in itself is considered an intensification by which the poet expresses his feelings, feelings and experiences, as well as the aspirations and desires of his society, through poetic verses full of meanings and images. The Arabs are from poetry, except for the verses that a man says in his need, but the poems and the length of poetry were intended during the era of Abd al-Muttalib and Hashim bin Abd Manaf)) ().Condensation linguistically: ((thickens: kaf, al-thaa’, and al-fa’a) is a valid origin that indicates the superposition of something upon something and gathering: it is said that this is a dense thing, dense clouds, and dense trees))().